An Sosialisasi Strategi Pemasaran Digital Pasca Panen Hidroponik Bagi Siswa Ekstrakulikuler Green Be di SMAN 1 Pemali - Rumalessin, Ummu Artha Tsary; Ali, Hendrik; Vera, Lusi Olis; Alamsyah, Redi; Pratama, Muhammad Setya; Gucchi, Anjaka Ray; Annafi, Ganif Nur (Jurnal Pengabdian kepada Masyarakat Politeknik Negeri Batam, 2025)
The agricultural sector continues to experience a decline in income, largely due to a mismatch between production capacity and the empowerment of farmers in post-harvest product marketing. This issue is exacerbated by the continued reliance on traditional marketing practices, which limit farmers' access to broader consumer markets. Thus, addressing this gap is critical for enhancing farmers' bargaining power by facilitating direct connections between producers and consumers. This community initiative aimed to enhance the capacity of millennial young farmers to digitally market post-harvest hydroponic agricultural products through the TikTok e-commerce platform. The program employed educational seminars and hands-on training focused on digital marketing strategies and the utilization of e-commerce tools. The participants comprised 30 students from SMAN 1 Pemali, all members of the "Green Be" extracurricular group. The result, conducted through semi-structured interview incorporating a combination of structured (closed-ended) and exploratory (open-ended) questions, indicated that 85% of participants demonstrated a significantly improved understanding of digital marketing concepts, including the marketing mix, promotion mix, and content creation. Moreover, participants reported increased proficiency in leveraging TikTok as a marketing platform for hydroponic agricultural products. These findings highlight the critical role of human resource development in advancing post-harvest agricultural marketing through innovative and sustainable digital strategies, contributing meaningfully to the broader objectives of Sustainable Agricultural Development.